Product Ratings and Online Reviews as Drivers of Purchase Decisions on TikTok Shop - Septian Bayu Arif Firmansyah; Deddy Junaedi (Lentera Ilmu Nusantara, 2026)
This study aims to examine the influence of Online Customer Reviews and Product Ratings on purchasing decisions in the TikTok Shop Marketplace among consumers in Karanganyar Village. The research employed a quantitative approach with an explanatory research design. The population consisted of residents of Karanganyar Village who had previously purchased products through TikTok Shop, while the sample comprised 96 respondents selected using purposive sampling. Data were collected through a five-point Likert-scale questionnaire. The research instruments met the validity and reliability requirements, and the data were analyzed using multiple linear regression with IBM SPSS Statistics. The findings reveal that Online Customer Reviews do not have a significant effect on purchasing decisions, with a significance value of 0.284 (>0.05). In contrast, Product Ratings have a positive and significant effect on purchasing decisions, with a significance value of 0.000 (<0.05). Simultaneously, Online Customer Reviews and Product Ratings significantly influence purchasing decisions, as indicated by an F-value of 40.008 and a significance level of 0.000. The coefficient of determination (R²) of 0.462 indicates that both independent variables explain 46.2% of the variation in purchasing decisions, while the remaining 53.8% is influenced by other factors outside the research model. These findings suggest that consumers on TikTok Shop rely more heavily on product ratings than customer reviews when making purchasing decisions.